Integrating Cooperative Learning Strategies in Teaching Arabic Reading Comprehension / دمج استراتيجيات التعلم التعاوني في تعليم مهارة الفهم القرائي باللغة العربية - Khofifah Fathim; Mansur Ahmadi (IJAS: International Journal of Arabic Studies, 2025)
This study investigates the effectiveness of integrating cooperative learning strategies in teaching Arabic reading comprehension. The research is motivated by the need to enhance students’ active engagement, improve their critical reading skills, and foster collaboration in multicultural classroom contexts. A qualitative and quantitative mixed-methods approach was employed, including classroom observations, structured interviews with teachers, and pre- and post-tests administered to students. The findings indicate that cooperative learning strategies, such as think-pair-share, jigsaw reading, and group discussion, significantly improved students’ comprehension, vocabulary acquisition, and motivation to read Arabic texts. Moreover, the study highlights that cooperative learning created a supportive learning environment that encouraged peer interaction and reduced anxiety among learners. The results underscore the importance of adopting student-centered approaches in Arabic language pedagogy, particularly in fostering reading comprehension as a foundation for advanced language proficiency. This research provides practical implications for Arabic educators and curriculum designers, suggesting that cooperative learning can be a powerful tool for achieving both linguistic and affective learning outcomes.